A very rare cause of acute pancreatitis: Berardinelli-Seip congenital lipodystrophy - İşlek, Ali and Sayar, Ersin and Yılmaz, Aygen and Duman, Özgür and Artan, Reha (Turkish Journal of Gastroenterology, 2014)
Abstract Pancreatitis is among rare diseases in pediatrics clinics. It is usually presented with a sign of underlying systemic disease. Berardinelli-Seip congenital lipodystrophy (BSCL) is a very rare disease characterized by near absence of adipose tissue resulting in apparent muscle hypertrophy from birth or early infancy associated with severe insulin resistance. Common clinical features are hypertriglyceridemia, acanthosis nigricans, hepatomegaly with or without splenomegaly and high stature. Acromegaloid features, cardiomyopathy and mental retardation can also be present. We describe a 7-year-old Turkish boy with these clinical features of BSCL and presented with acute pancreatitis.